THE IMPLEMENTATION OF THE POLICY OF EARLY CHILDHOOD EDUCATION NONFORMAL IN SUB-DISTRICT BANYUMANIK THE CITY OF SEMARANG - Pradipta, Pandu; Dwimawanti, Ida Hayu; Rengga, Aloysius (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Early childhood education is a series of effort systematically and programmed to doing coaching for birth year until six years old. through the provision of educational stimuli to help physical as well as spiritual growth in order for the child to have the readiness to enter further education. Early childhood education lane nonformal education : Play group, Children's Daycare, Similar Play Group, or any other form of equal. Play Group (KB) is one form of early childhood education in non-formal education channels at the same time conducting a welfare educational program for children aged 2 to 4 years. The target of Play Group is age of 2-4 years and children aged 4-6 years who can not be served TK (after a recommendation from the authorities). The period of early childhood is a golden age that will not be repeated, as it is the most important period in the formation of the basics of personality, thinking, intelligence, skills, and social skills. So that basic education for children should be as early as possible, not only at the age of 9 years of education, after most of the possible development of children's potential began to decrease. The study was designed and analyzed qualitatively dekscriptif. The data was collected by way of literature study, observation and in-depth interviews with a number of informants.This study describes and analyzes the implementation of the Non-formal Early Childhood Education in Banyumanik, Semarang. Learners, teachers, teacher competence, aspects of child development, and the infrastructure is in issue in the implementation of the Non-formal early childhood policies.It can be concluded implementation of Early Childhood Education Policy in Banyumanik, Semarang still find problems. This can be seen from the discovery of some problems in qualifying teachers.there is still the persistence of the teachers do not have the competence to give guidance to children. still found that early childhood education has not met the standards of facilities and infrastructure in organizing early childhood education. Discovery of factors inhibiting such a limited number of officers to serve the early childhood units and less effective communication between the Department of Education with Early Childhood Unit. So it needs to be fixed.